2006
DOI: 10.2527/2006.8441022x
|View full text |Cite
|
Sign up to set email alerts
|

Comparison of grain sources for swine diets and their effect on meat and fat quality traits1

Abstract: A study was conducted to evaluate the effect of dietary grain sources on various compositional and quality characteristics of pork from pigs reared in a commercial environment. Pigs were fed 1 of 5 dietary treatments containing the following single or blended grain sources throughout most of the grow-finish period: 1) yellow corn, 2) white corn, 3) 1/3 yellow corn and 2/3 white corn, 4) 2/3 yellow corn and 1/3 white corn, and 5) barley. Pigs were from 2 sire genetic types, Duroc and Hampshire x Duroc, mated to… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
20
0

Year Published

2010
2010
2024
2024

Publication Types

Select...
6
3
1

Relationship

0
10

Authors

Journals

citations
Cited by 23 publications
(21 citation statements)
references
References 11 publications
1
20
0
Order By: Relevance
“…There exist controversial data about the effects of the replacement of corn with other cereal grains with lower C18:2n-6 content on pig fat hardness (Johnston and Li, 2011). In agreement with our results, Lampe et al (2006) found that barley reduced PUFA content and increased the SFA level of SC. Carr et al (2005) found no differences in the fatty acid composition of carcass fat when comparing corn, wheat, and barley in pig diets.…”
Section: Discussionsupporting
confidence: 93%
“…There exist controversial data about the effects of the replacement of corn with other cereal grains with lower C18:2n-6 content on pig fat hardness (Johnston and Li, 2011). In agreement with our results, Lampe et al (2006) found that barley reduced PUFA content and increased the SFA level of SC. Carr et al (2005) found no differences in the fatty acid composition of carcass fat when comparing corn, wheat, and barley in pig diets.…”
Section: Discussionsupporting
confidence: 93%
“…), whereas Lampe et al . () indicated that barley has greater levels of SFA and MUFA, and lower levels of unsaturated fatty acids and PUFA, in the subcutaneous fat of pigs fed maize diets. In our study, the water‐soaked barley improved PUFA content and decreased SFA contents in the LM.…”
Section: Discussionmentioning
confidence: 99%
“…Because a growing percentage of U.S. pork is exported to international markets, sorghum DDGS may have an important role in the future of swine diets because of its ability to produce pork fat that is lighter in color and less yellow. Previous research conducted to determine the effects of diet composition on fat color found no differences when feeding barley or yellow or white corn, but the barley-based diet was found to produce harder fat compared with yellow and white corn-based diets (Lampe et al, 2006). Xu et al (2010) observed no differences for fat a* for pigs fed increasing corn DDGS, but pigs fed DDGS had darker fat (L*) and increased yellowness (b*) compared with pigs fed the corn-based control diet.…”
Section: Discussionmentioning
confidence: 90%